Novel titanium-zirconium-based superhard tool coating as well as preparation method and application thereof
Patent Information
- Application Number
- CN202411277279.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
AI Technical Summary
The existing tool coatings have low hardness, weak wear resistance and weak crack resistance in high-temperature and high-pressure environments, making it difficult to meet the high-performance needs of high-speed cutting processing.
Using the preparation method of titanium-zirconium-based superhard tool coating, the TiZrAlCrN and TiZrAlCrSiN composite layers are deposited by introducing a transition layer with varying composition gradients to form an adhesive layer, transition layer and functional layer, which improves the bonding strength and oxidation resistance of the coating. .
It significantly improves the high temperature hardness, wear resistance and oxidation resistance of the coating, extends the service life of the tool, and shows excellent cutting performance under dry cutting conditions.
Smart Images

Figure CN119121142A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of tool coatings, and in particular to a novel titanium-zirconium-based superhard tool coating and a preparation method and application thereof. Background Art
[0002] As an advanced manufacturing technology, high-speed cutting has made great contributions to high-precision manufacturing. Compared with conventional cutting technology, it combines high efficiency, high quality and low consumption. During the cutting process, high-speed machining will inevitably generate a lot of heat. In order to ensure the normal use of cutting tools, most mechanical processing chooses to add cutting fluid to reduce the temperature. However, the high temperature generated during the processing causes the cutting fluid to evaporate in a mist form, which seriously pollutes the environment and threatens the health of the operator. In order to promote the green transformation of high-speed cutting, dry cutting technology is proposed. However, dry cutting technology is a process of grinding without cooling conditions. It lacks the cooling, lubrication and chip removal functions of the cutting fluid. The friction area between the tool and the workpiece in the grinding area increases, the cutting resistance increases, the grinding vibration increases, and the chip removal is not smooth, which greatly reduces the surface quality of the workpiece and the service life of the tool.
[0003] To overcome these problems, it is usually necessary to treat the surface of the tool and deposit a protective coating on the tool surface through physical vapor deposition technology. This coating can improve the performance of the tool and extend its service life. However, for traditional tool coatings, such as TiN, CrN and TiAlN, it has gradually been found that they are difficult to meet these strict performance standards. The performance of these traditional coatings may decline in high temperature and high pressure environments, and thus cannot meet higher use requirements. Therefore, it is necessary to develop new coating materials and preparation technologies to meet the performance requirements of tools in high temperature and high pressure environments.
[0004] In the Chinese patent with application number 202310681051.4, a bonding layer with good toughness and low hardness is set between the tool substrate and the multi-layer coating to improve the bonding strength of the coating. However, the transition layer is single, the composition difference between the bonding layer and the periodic composite layer is large, there is a difference in thermal expansion coefficient, and the coating is prone to cracking during use and fails prematurely; the thickness of the bonding layer is too thin, although it can improve the bonding strength, it cannot provide a good support for the composite alternating layer and the functional layer, which can easily cause the coating to fail early. The hardness of the coating after high-temperature annealing is a major mechanical parameter of the thermal stability of the coating structure, and it is also an important indicator of whether it can be used for a long time. The Al-based coating of this invention has excellent antioxidant properties, but the mechanical properties are insufficient at high temperatures, and it is easy to wear during tool cutting. In the Chinese patent with application number 201680023831.8, the hardness of the embodiment is shown as 2200HV-3200HVG, which is low and the wear resistance needs to be improved; the purpose of the invention is to improve the anti-adhesion performance during the cutting of titanium alloys; the coating composition of the invention is mainly Al element, and it has excellent antioxidant properties, but the mechanical properties are insufficient at high temperatures, and the tool is prone to wear during cutting; the embodiment shows that the coating thickness is about 3um, the coating thickness is relatively thin, and the impact resistance needs to be improved; in the coating preparation process, the coating is directly plated after Ar ion etching, and the bonding strength needs to be improved in order to design the hardness gradient result. In the Chinese patent with application number 202310559774.7, magnetron sputtering is used. It can be seen from the attached figure of the embodiment that the bonding strength (Lc1) between the coating and the substrate is weak. The embodiment before oxidation is less than 5N, and the crack resistance is weak; the hardness of the embodiment is only 28.8GPa, and the wear resistance needs to be improved; the coating thickness is thin, and the embodiment shows that it is only about 1um, and the impact resistance is not strong; during the coating preparation process, 3 groups of target materials are sputtered simultaneously, the process is complicated, and the repetition rate is low. Summary of the invention
[0005] The present invention designs and develops a novel titanium-zirconium-based superhard tool coating, the purpose of which is to solve the problems of low high-temperature hardness, weak wear resistance and weak crack resistance of existing tool coatings.
[0006] The present invention designs and develops a novel method for preparing titanium zirconium-based superhard tool coatings. The purpose of the present invention is to provide a method for preparing a superhard, tough, and high-temperature resistant tool coating material by introducing a transition layer with a gradient composition change during the preparation process to composite TiZrAlCrN and TiZrAlCrSiN.
[0007] The present invention designs and develops an application of a novel titanium-zirconium-based superhard tool coating, and the purpose of the present invention is to solve the application problem of superhard, tough and high-temperature resistant tool coating.
[0008] The technical solution provided by the present invention is:
[0009] A method for preparing a novel titanium-zirconium-based superhard tool coating comprises the following steps:
[0010] Step 1: After cleaning the sample to be plated, place it in a coating furnace, evacuate the vacuum, heat the substrate, and perform ion implantation;
[0011] Step 2, adjusting the argon flow rate to maintain the vacuum state, turning on the TiZrAlCr target arc power supply to deposit the TiZrAlCr layer, turning off the TiZrAlCr target arc power supply, turning on the TiZrAlCrSi target arc power supply to deposit the TiZrAlCrSi layer, and turning off the TiZrAlCrSi target arc power supply after the bonding layer is formed;
[0012] Step 3, adjusting the flow rate of nitrogen and argon to maintain the vacuum state, turning on the TiZrAlCr target arc power supply to deposit the TiZrAlCrN layer, turning off the TiZrAlCr target arc power supply, turning on the TiZrAlCrSi target arc power supply to deposit the TiZrAlCrSiN layer, and turning off the TiZrAlCrSi target arc power supply after the transition layer is formed;
[0013] Step 4: Turn on the TiZrAlCr target arc power supply and the TiZrAlCrSi target arc power supply at the same time, deposit the TiZrAlCrN / TiZrAlCrSiN layer, and cool after forming the functional layer to obtain the novel titanium-zirconium-based superhard tool coating.
[0014] Preferably, in step 1, the cleaning process of the sample to be plated comprises: immersing the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-drying the surface; and
[0015] Vacuum to 5×10 -2 Pa, heat to 400-500℃ and keep warm for 60min.
[0016] Preferably, in step 1, the ion implantation conditions include: selecting Ti as the cathode, an extraction voltage of 10-15 kV, a trigger frequency of 0-15 Hz, controlling the target current to 80-120 mA, and an implantation time of 30 min.
[0017] Preferably, in the step 2, the coating rotation speed is set to 1 r / min, and the vacuum state is maintained at 1.0-1.2 Pa.
[0018] Preferably, in step three, the coating rotation speed is set to 1 r / min, the vacuum state is maintained at 2.4-3.6 Pa, and the partial pressure ratio of nitrogen and argon is 1:2.
[0019] Preferably, in step 4, the rotation speed is set to increase from 1 r / min to 5 r / min before the coating is finished, the vacuum state is maintained at 2.4-3.6 Pa, and the partial pressure ratio of nitrogen and argon is 1:2.
[0020] Preferably, the TiZrAlCr target is Ti p Zr q Al r Cr s , where p, q, r, s satisfy 0.40≤p≤0.55, 0.25≤q≤0.35, 0.10≤r≤0.25, 0.05≤s≤0.10, p+q+r+s=1, current is 90~120A, bias voltage is -50~-350V, and lasts for 2~10min;
[0021] Set the TiZrAlCrSi target to Ti a Zr b Al c Cr d Si e , where a, b, c, d, e, satisfy 0.40≤a≤0.55, 0.25≤b≤0.35, 0.10≤c≤0.25, d=0.05, e=0.05, a+b+c+d+e=1, current is 90~120A, bias voltage is -50~-350V, and lasts for 2~10min; and
[0022] Among them, 0≤|pa|≤0.15, 0≤|qb|≤0.15, 0≤|rc|≤0.15, 0≤|sd|≤0.10.
[0023] A novel titanium zirconium-based superhard tool coating is prepared using the novel titanium zirconium-based superhard tool coating preparation method, wherein the novel titanium zirconium-based superhard tool coating comprises a bonding layer, a transition layer and a functional layer deposited in sequence;
[0024] Wherein, the bonding layer comprises a TiZrAlCr layer and a TiZrAlCrSi layer deposited sequentially, the transition layer comprises a TiZrAlCrN layer and a TiZrAlCrSiN layer deposited sequentially, and the functional layer comprises a TiZrAlCrN layer and a TiZrAlCrSiN layer deposited periodically and alternately; and
[0025] The chemical composition and mass percentage of the TiZrAlCr layer are: Ti: 40% to 55%, Zr: 25% to 35%, Al: 10% to 25%, Cr: 5% to 10%;
[0026] The chemical composition and mass percentage of the TiZrAlCrSi layer are: Ti: 40% to 55%, Zr: 25% to 35%, Al: 10% to 25%, Cr: 5%, Si: 5%;
[0027] The chemical composition and mass percentage of the TiZrAlCrN layer are: Ti: 20% to 27.5%, Zr: 12.5% to 17.5%, Al: 5% to 12.5%, Cr: 2.5% to 5%, N: 50%;
[0028] The chemical composition and mass percentage of the TiZrAlCrSiN layer are: Ti: 20% to 27.5%, Zr: 12.5% to 17.5%, Al: 5% to 12.5%, Cr: 2.5%, Si: 2.5%, and N: 50%.
[0029] Preferably, the novel titanium-zirconium-based superhard tool coating has a thickness of 3 to 6 um.
[0030] The invention discloses an application of a novel titanium-zirconium-based superhard tool coating in a superhard, strong, and high-temperature-resistant cutting tool, and uses the novel titanium-zirconium-based superhard tool coating.
[0031] The beneficial effects of the present invention are:
[0032] 1. In the composition of the novel titanium-zirconium-based superhard tool coating provided by the present invention, the TiZr-based coating, at high temperature, the Zr element directly promotes the formation of thermodynamically stable rutile TiO2, and further leads to the formation of a dense TiO2-based structure (when Zr replaces Ti in TiO2 to form (Ti, Zr)O2), thereby increasing the high-temperature mechanical properties of the coating (high-temperature hardness and high-temperature wear resistance); the introduction of a small-radius Si element, in which the Si element mainly exists in the amorphous form of Si3N4, makes the coating gradually dense and increases the hardness of the coating; Al and Cr will generate Al2O3 and Cr2O3 protective oxide layers during the oxidation process, which can effectively prevent further diffusion of oxygen into the cemented carbide, thereby ensuring the high oxidation resistance of the coating; the prepared coating has a high mixing entropy, tends to form a simple solid solution or an amorphous structure, and can meet the strengthening requirements of high-entropy alloys;
[0033] 2. In the novel titanium-zirconium-based superhard tool coating structure provided by the present invention, a thick bonding layer is introduced to improve the impact resistance and avoid the eggshell effect; a transition layer with a gradient composition change (Si content change) is introduced to form a gradient transition of the thermal expansion coefficient, thereby increasing the bonding strength and anti-cracking ability;
[0034] 3. In the preparation method of the new titanium-zirconium-based superhard tool coating provided by the present invention, by adjusting the rotating speed of the rotating frame (1r / min-5r / min), a single layer of nano-coating with a thickness of more than 50nm-25nm is alternately deposited to realize the gradient structure preparation of the functional layer. The functional layer part close to the surface forms a nano-multilayer structure, which can produce an obvious "superlattice" strengthening effect, thereby increasing the hardness of the coating and inhibiting the interlayer expansion of cracks. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a schematic diagram of the structure of the novel titanium-zirconium-based superhard tool coating according to the present invention;
[0036] Figure 2a This is a surface morphology of the new titanium-zirconium-based superhard tool coating prepared in Example 1 of the present invention;
[0037] Figure 2b This is a nanohardness curve of the novel titanium-zirconium-based superhard tool coating prepared in Example 1 of the present invention;
[0038] Figure 2c This is a cross-sectional morphology of the novel titanium-zirconium-based superhard tool coating prepared in Example 1 of the present invention;
[0039] Figure 3a This is a surface morphology of the new titanium-zirconium-based superhard tool coating prepared in Example 2 of the present invention;
[0040] Figure 3b This is a nanohardness curve of the new titanium-zirconium-based superhard tool coating prepared in Example 2 of the present invention;
[0041] Figure 3c This is a cross-sectional morphology of a novel titanium-zirconium-based superhard tool coating prepared in Example 2 of the present invention;
[0042] Figure 4a This is a surface morphology of the new titanium-zirconium-based superhard tool coating prepared in Example 3 of the present invention;
[0043] Figure 4b This is a nanohardness curve of the new titanium-zirconium-based superhard tool coating prepared in Example 3 of the present invention;
[0044] Figure 4c This is a cross-sectional morphology of a novel titanium-zirconium-based superhard tool coating prepared in Example 3 of the present invention;
[0045] Figure 5a This is a surface morphology of the new titanium-zirconium-based superhard tool coating prepared in Example 4 of the present invention;
[0046] Figure 5bThis is a nanohardness curve of the novel titanium-zirconium-based superhard tool coating prepared in Example 4 of the present invention;
[0047] Figure 5c This is a cross-sectional morphology of a novel titanium-zirconium-based superhard tool coating prepared in Example 4 of the present invention;
[0048] Figure 6a This is a surface morphology of the new titanium-zirconium-based superhard tool coating prepared in Example 5 of the present invention;
[0049] Figure 6b This is a nanohardness curve of the novel titanium-zirconium-based superhard tool coating prepared in Example 5 of the present invention;
[0050] Figure 6c This is a cross-sectional morphology of a novel titanium-zirconium-based superhard tool coating prepared in Example 5 of the present invention;
[0051] Figure 7 This is a comparison chart of the cutting life of the new titanium-zirconium-based superhard tool coating prepared in Examples 1 to 5 of the present invention after being applied to a tool;
[0052] Figure 8 This is a comparison chart of the film-substrate bonding strength of the novel titanium-zirconium-based superhard tool coatings prepared in Examples 1 to 5 described in the present invention. DETAILED DESCRIPTION
[0053] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0054] like Figure 1 As shown, the present invention provides a novel titanium-zirconium-based superhard tool coating, comprising: a bonding layer 110, a transition layer 120 and a functional layer 130 coated on a substrate 100; wherein the bonding layer 110 specifically comprises a TiZrAlCr layer and a TiZrAlCrSi layer deposited in sequence, the transition layer 120 specifically comprises a TiZrAlCrN layer and a TiZrAlCrSiN layer deposited in sequence, and the functional layer 130 specifically comprises a TiZrAlCrN layer and a TiZrAlCrSiN layer deposited periodically and alternately;
[0055] The chemical composition and mass percentage of the TiZrAlCr layer are: Ti: 40% to 55%, Zr: 25% to 35%, Al: 10% to 25%, Cr: 5% to 10%;
[0056] The chemical composition and mass percentage of the TiZrAlCrSi layer are: Ti: 40% to 55%, Zr: 25% to 35%, Al: 10% to 25%, Cr: 5%, Si: 5%;
[0057] The chemical composition and mass percentage of the TiZrAlCrN layer are: Ti: 20% to 27.5%, Zr: 12.5% to 17.5%, Al: 5% to 12.5%, Cr: 2.5% to 5%, N: 50%;
[0058] The chemical composition and mass percentage of the TiZrAlCrSiN layer are: Ti: 20% to 27.5%, Zr: 12.5% to 17.5%, Al: 5% to 12.5%, Cr: 2.5%, Si: 2.5%, and N: 50%.
[0059] The present invention provides a method for preparing a novel titanium-zirconium-based superhard tool coating, comprising the following steps:
[0060] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0061] Step 2: MEVVA ion implantation: Place the cleaned sample into the coating furnace and evacuate to 5×10 -2 After Pa, the auxiliary heating source is turned on, the substrate is heated to 400-500℃ and kept warm for 60min, and then the MEVVA power supply is turned on for ion implantation; wherein, the parameter settings are: the cathode is selected as Ti, the extraction voltage is 10-15kV, the trigger frequency is 0-15Hz, the target current is controlled to 80-12mA, and the injection time is 30min;
[0062] Step 3: After the injection is completed, the bonding layer 110 is deposited: the rotation speed is set to 1 r / min, the argon flow rate is adjusted to maintain the vacuum at 1.0-1.2 Pa, and the TiZrAlCr target arc power supply is turned on to deposit the TiZrAlCr layer 111. The target material is Ti p Zr q Al r Cr s , where p, q, r, and s satisfy 0.40≤p≤0.55, 0.25≤q≤0.35, 0.10≤r≤0.25, 0.05≤s≤0.10, p+q+r+s=1, the current is set to 90~120A, the bias voltage is -50~-350V, and the duration is 2~10min; the TiZrAlCr target arc power supply is turned off, and the TiZrAlCrSi target arc power supply is turned on to deposit the TiZrAlCrSi layer 112, and the target material is Ti a Zr b Al c Cr d Si e, where a, b, c, d, e, satisfy 0.40≤a≤0.55, 0.25≤b≤0.35, 0.10≤c≤0.25, d=0.05, e=0.05, a+b+c+d+e=1, set the current to 90~120A, bias voltage -50~-350V, last for 2~10min; after sequential deposition to form the bonding layer 110, turn off the TiZrAlCrSi target arc power supply; where 0≤|pa|≤0.15, 0≤|qb|≤0.15, 0≤|rc|≤0.15, 0≤|sd|≤0.10;
[0063] Step 4: Deposit transition layer 120: Set the rotation speed to 1 r / min, adjust the flow rate of nitrogen and argon, maintain the vacuum to 2.4-3.6 Pa (nitrogen and argon partial pressure ratio is 1:2), turn on the TiZrAlCr target arc power supply to deposit TiZrAlCrN layer 121, the target material is Ti p Zr q Al r Cr s , where p, q, r, and s satisfy 0.40≤p≤0.55, 0.25≤q≤0.35, 0.10≤r≤0.25, 0.05≤s≤0.10, p+q+r+s=1, the current is set to 90~120A, the bias voltage is -50~-350V, and the duration is 20~60min; turn off the TiZrAlCr target arc power supply, turn on the TiZrAlCrSi target arc power supply to deposit the TiZrAlCrSiN layer 122, and the target material is Ti a Zr b Al c Cr d Si e , where a, b, c, d, e, satisfy 0.40≤a≤0.55, 0.25≤b≤0.35, 0.10≤c≤0.25, d=0.05, e=0.05, a+b+c+d+e=1, set the current to 90~120A, bias voltage -50~-350V, last for 20~60min; after sequentially depositing to form transition layer 120, turn off the TiZrAlCrSi target arc power supply; where 0≤|pa|≤0.15, 0≤|qb|≤0.15, 0≤|rc|≤0.15, 0≤|sd|≤0.10;
[0064] Step 5: Deposit the functional layer 130: Turn on the TiZrAlCr target arc power supply, the target material is Ti p Zr q Al r Cr s, where p, q, r, and s satisfy 0.40≤p≤0.55, 0.25≤q≤0.35, 0.10≤r≤0.25, 0.05≤s≤0.10, p+q+r+s=1, and the arc power supply of the TiZrAlCrSi target is turned on at the same time. The target material is Ti a Zr b Al c Cr d Si e , where a, b, c, d, e, satisfy 0.40≤a≤0.55, 0.25≤b≤0.35, 0.10≤c≤0.25, d=0.05, e=0.05, a+b+c+d+e=1, the rotation speed is set to increase from 1r / min to 5r / min at the end of the coating, the current is set to 90~120A, the bias voltage is -50~-350V, the duration is 80~120min, and the functional layer 130 is formed by periodic alternating deposition, including a periodic alternating deposition of TiZrAlCrN layer and TiZrAlCrSiN layer; wherein 0≤|pa|≤0.15, 0≤|qb|≤0.15, 0≤|rc|≤0.15, 0≤|sd|≤0.10;
[0065] Step 6: After the coating is completed, the film is cooled in the furnace and then taken out of the furnace to complete the preparation.
[0066] The present invention will be further described below in conjunction with specific embodiments.
[0067] Example 1
[0068] The present invention provides a novel method for preparing a titanium-zirconium-based superhard tool coating, comprising the following steps:
[0069] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0070] Step 2: MEVVA ion implantation: Place the cleaned sample into the coating furnace and evacuate to 5×10 -2 After Pa, the auxiliary heating source is turned on, the substrate is heated to 400-500℃ and kept warm for 60min, and then the MEVVA power supply is turned on for ion implantation; wherein, the parameter settings are: the cathode is selected as Ti, the extraction voltage is 10-15kV, the trigger frequency is 0-15Hz, the target current is controlled to 80-12mA, and the injection time is 30min;
[0071] Step 3: After the injection is completed, deposit the bonding layer: set the rotation speed to 1r / min, adjust the argon flow rate to maintain the vacuum at 1.0-1.2Pa, turn on the TiZrAlCr target arc power supply to deposit the TiZrAlCr layer, and the target material is Ti 0.40 Zr0.25 Al 0.25 Cr 0.10 , set the current to 90~120A, bias voltage -50~-350V, and last for 2~10min; turn off the TiZrAlCr target arc power supply, turn on the TiZrAlCrSi target arc power supply to deposit the TiZrAlCrSi layer, the target material is Ti 0.4 Zr 0.25 Al 0.25 Cr 0.05 Si 0.05 , set the current to 90~120A, bias voltage -50~-350V, and continue for 2~10min; after the bonding layer is formed, turn off the TiZrAlCrSi target arc power supply;
[0072] Step 4: Deposit the transition layer: Set the rotation speed to 1r / min, adjust the flow rate of nitrogen and argon, maintain the vacuum to 2.4Pa (nitrogen-argon partial pressure ratio is 1:2), turn on the TiZrAlCr target arc power supply to deposit the TiZrAlCrN layer, and the target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.10 , set the current to 90~120A, bias voltage -50~-350V, duration 20min; turn off the TiZrAlCr target arc power supply, turn on the TiZrAlCrSi target arc power supply to deposit the TiZrAlCrSiN layer, the target material is Ti 0.4 Zr 0.25 Al 0.25 Cr 0.05 Si 0.05 , set the current to 90~120A, bias voltage -50~-350V, and continue for 20min; after the transition layer is formed, turn off the TiZrAlCrSi target arc power supply;
[0073] Step 5: Deposition of functional layer: Turn on the arc power supply of TiZrAlCr target, the target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.10 , and turn on the TiZrAlCrSi target arc power supply at the same time. The target material is Ti 0.4 Zr 0.25 Al 0.25 Cr 0.05 Si 0.05 , set the rotation speed to increase from 1r / min to 5r / min at the end of coating, set the current to 90-120A, the bias voltage to -50--350V, the duration to 120min, and deposit TiZrAlCrN / TiZrAlCrSiN functional layer;
[0074] Step 6: After the coating is completed, the film is cooled in the furnace and then taken out of the furnace to complete the preparation.
[0075] The novel titanium-zirconium-based superhard tool coating prepared in this embodiment includes a bonding layer, a transition layer and a functional layer deposited in sequence; the bonding layer includes a TiZrAlCr layer and a TiZrAlCrSi layer deposited in sequence, the transition layer includes a TiZrAlCrN layer and a TiZrAlCrSiN layer deposited in sequence, and the functional layer includes a periodically alternately deposited TiZrAlCrN layer and a TiZrAlCrSiN layer;
[0076] Among them, the chemical composition and mass percentage of the TiZrAlCr layer are: Ti: 40%, Zr: 25%, Al: 25%, Cr: 10%; the chemical composition and mass percentage of the TiZrAlCrSi layer are: Ti: 40%, Zr: 25%, Al: 25%, Cr: 5%, Si: 5%; the chemical composition and mass percentage of the TiZrAlCrN layer are: Ti: 20%, Zr: 12.5%, Al: 12.5%, Cr: 5%, N: 50%; the chemical composition and mass percentage of the TiZrAlCrSiN layer are: Ti: 20%, Zr: 12.5%, Al: 12.5%, Cr: 2.5%, Si: 2.5%, N: 50%.
[0077] Example 2
[0078] The present invention provides a novel method for preparing a titanium-zirconium-based superhard tool coating, comprising the following steps:
[0079] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0080] Step 2: MEVVA ion implantation: Place the cleaned sample into the coating furnace and evacuate to 5×10 -2 After Pa, the auxiliary heating source is turned on, the substrate is heated to 400-500℃ and kept warm for 60min, and then the MEVVA power supply is turned on for ion implantation; wherein, the parameter settings are: the cathode is selected as Ti, the extraction voltage is 10-15kV, the trigger frequency is 0-15Hz, the target current is controlled to 80-12mA, and the injection time is 30min;
[0081] Step 3: After the injection is completed, deposit the bonding layer: set the rotation speed to 1r / min, adjust the argon flow rate to maintain the vacuum at 1.0-1.2Pa, turn on the TiZrAlCr target arc power supply to deposit the TiZrAlCr layer, and the target material is Ti 0.40 Zr 0.30 Al 0.20 Cr 0.10, set the current to 90~120A, bias voltage -50~-350V, and last for 2~10min; turn off the TiZrAlCr target arc power supply, turn on the TiZrAlCrSi target arc power supply to deposit the TiZrAlCrSi layer, the target material is Ti 0.55 Zr 0.25 Al 0.10 Cr 0.05 Si 0.05 , set the current to 90~120A, bias voltage -50~-350V, and continue for 2~10min; after the bonding layer is formed, turn off the TiZrAlCrSi target arc power supply;
[0082] Step 4: Deposit the transition layer: Set the rotation speed to 1r / min, adjust the flow rate of nitrogen and argon, maintain the vacuum to 2.4Pa (nitrogen-argon partial pressure ratio is 1:2), turn on the TiZrAlCr target arc power supply to deposit the TiZrAlCrN layer, and the target material is Ti 0.40 Zr 0.30 Al 0.20 Cr 0.10 , set the current to 90~120A, bias voltage -50~-350V, duration 30min; turn off the TiZrAlCr target arc power supply, turn on the TiZrAlCrSi target arc power supply to deposit the TiZrAlCrSiN layer, the target material is Ti 0.55 Zr 0.25 Al 0.10 Cr 0.05 Si 0.05, Set the current to 90-120A, bias voltage to -50-350V, and continue for 30min; after the transition layer is formed, turn off the TiZrAlCrSi target arc power supply;
[0083] Step 5: Deposition of functional layer: Turn on the arc power supply of TiZrAlCr target, the target material is Ti 0.40 Zr 0.30 Al 0.20 Cr 0.10 , and turn on the TiZrAlCrSi target arc power supply at the same time. The target material is Ti 0.55 Zr 0.25 Al 0.10 Cr 0.05 Si 0.05 , set the rotation speed to increase from 1r / min to 5r / min at the end of coating, set the current to 90-120A, the bias voltage to -50--350V, the duration to 110min, and deposit TiZrAlCrN / TiZrAlCrSiN functional layer;
[0084] Step 6: After the coating is completed, the film is cooled in the furnace and then taken out of the furnace to complete the preparation.
[0085] The novel titanium-zirconium-based superhard tool coating prepared in this embodiment includes a bonding layer, a transition layer and a functional layer deposited in sequence; the bonding layer includes a TiZrAlCr layer and a TiZrAlCrSi layer deposited in sequence, the transition layer includes a TiZrAlCrN layer and a TiZrAlCrSiN layer deposited in sequence, and the functional layer includes a periodically alternately deposited TiZrAlCrN layer and a TiZrAlCrSiN layer;
[0086] Among them, the chemical composition and mass percentage of the TiZrAlCr layer are: Ti: 40%, Zr: 30%, Al: 20%, Cr: 10%; the chemical composition and mass percentage of the TiZrAlCrSi layer are: Ti: 55%, Zr: 25%, Al: 10%, Cr: 5%, Si: 5%; the chemical composition and mass percentage of the TiZrAlCrN layer are: Ti: 20%, Zr: 15%, Al: 10%, Cr: 5%, N: 50%; the chemical composition and mass percentage of the TiZrAlCrSiN layer are: Ti: 27.5%, Zr: 12.5%, Al: 5%, Cr: 2.5%, Si: 2.5%, N: 50%.
[0087] Example 3
[0088] The present invention provides a method for preparing a novel titanium-zirconium-based superhard tool coating, comprising the following steps:
[0089] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0090] Step 2: MEVVA ion implantation: Place the cleaned sample into the coating furnace and evacuate to 5×10 -2 After Pa, the auxiliary heating source is turned on, the substrate is heated to 400-500℃ and kept warm for 60min, and then the MEVVA power supply is turned on for ion implantation; wherein, the parameter settings are: the cathode is selected as Ti, the extraction voltage is 10-15kV, the trigger frequency is 0-15Hz, the target current is controlled to 80-12mA, and the injection time is 30min;
[0091] Step 3: After the injection is completed, deposit the bonding layer: set the rotation speed to 1r / min, adjust the argon flow rate to maintain the vacuum at 1.0-1.2Pa, turn on the TiZrAlCr target arc power supply to deposit the TiZrAlCr layer, and the target material is Ti 0.45 Zr 0.35 Al 0.15 Cr 0.05, set the current to 90~120A, bias voltage -50~-350V, and last for 2~10min; turn off the TiZrAlCr target arc power supply, turn on the TiZrAlCrSi target arc power supply to deposit the TiZrAlCrSi layer, the target material is Ti 0.45 Zr 0.35 Al 0.10 Cr 0.05 Si 0.05 , set the current to 90~120A, bias voltage -50~-350V, and continue for 2~10min; after the bonding layer is formed, turn off the arc power supply of TiZrAlCrSi target;
[0092] Step 4: Deposit transition layer: Set the rotation speed to 1r / min, adjust the flow rate of nitrogen and argon, maintain the vacuum to 3.0Pa (nitrogen and argon partial pressure ratio is 1:2), turn on the TiZrAlCr target arc power supply to deposit the TiZrAlCrN layer, and the target material is Ti 0.45 Zr 0.35 Al 0.15 Cr 0.05 , set the current to 90~120A, bias voltage -50~-350V, duration 40min; turn off the TiZrAlCr target arc power supply, turn on the TiZrAlCrSi target arc power supply to deposit the TiZrAlCrSiN layer, the target material is Ti 0.45 Zr 0.35 Al 0.10 Cr 0.05 Si 0.05 , set the current to 90~120A, bias voltage -50~-350V, and continue for 40min; after the transition layer is formed, turn off the TiZrAlCrSi target arc power supply;
[0093] Step 5: Deposition of functional layer: Turn on the arc power supply of TiZrAlCr target, the target material is Ti 0.45 Zr 0.35 Al 0.15 Cr 0.05 , and turn on the TiZrAlCrSi target arc power supply at the same time. The target material is Ti 0.45 Zr 0.35 Al 0.10 Cr 0.05 Si 0.05 , set the rotation speed to increase from 1r / min to 5r / min at the end of coating, set the current to 90-120A, the bias voltage to -50--350V, the duration to 100min, and deposit TiZrAlCrN / TiZrAlCrSiN functional layer;
[0094] Step 6: After the coating is completed, the film is cooled in the furnace and then taken out of the furnace to complete the preparation.
[0095] The novel titanium-zirconium-based superhard tool coating prepared in this embodiment includes a bonding layer, a transition layer and a functional layer deposited in sequence; the bonding layer includes a TiZrAlCr layer and a TiZrAlCrSi layer deposited in sequence, the transition layer includes a TiZrAlCrN layer and a TiZrAlCrSiN layer deposited in sequence, and the functional layer includes a periodically alternately deposited TiZrAlCrN layer and a TiZrAlCrSiN layer;
[0096] Among them, the chemical composition and mass percentage of the TiZrAlCr layer are: Ti: 45%, Zr: 35%, Al: 15%, Cr: 5%; the chemical composition and mass percentage of the TiZrAlCrSi layer are: Ti: 45%, Zr: 35%, Al: 10%, Cr: 5%, Si: 5%; the chemical composition and mass percentage of the TiZrAlCrN layer are: Ti: 22.5%, Zr: 17.5%, Al: 7.5%, Cr: 2.5%, N: 50%; the chemical composition and mass percentage of the TiZrAlCrSiN layer are: Ti: 22.5%, Zr: 17.5%, Al: 5%, Cr: 2.5%, Si: 2.5%, N: 50%.
[0097] Example 4
[0098] The present invention provides a method for preparing a novel titanium-zirconium-based superhard tool coating, comprising the following steps:
[0099] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0100] Step 2: MEVVA ion implantation: Place the cleaned sample into the coating furnace and evacuate to 5×10 -2 After Pa, the auxiliary heating source is turned on, the substrate is heated to 400-500℃ and kept warm for 60min, and then the MEVVA power supply is turned on for ion implantation; wherein, the parameter settings are: the cathode is selected as Ti, the extraction voltage is 10-15kV, the trigger frequency is 0-15Hz, the target current is controlled to 80-12mA, and the injection time is 30min;
[0101] Step 3: After the injection is completed, deposit the bonding layer: set the rotation speed to 1r / min, adjust the argon flow rate to maintain the vacuum at 1.0-1.2Pa, turn on the TiZrAlCr target arc power supply to deposit the TiZrAlCr layer, and the target material is Ti 0.50 Zr 0.25 Al 0.15 Cr 0.10, set the current to 90~120A, bias voltage -50~-350V, and last for 2~10min; turn off the TiZrAlCr target arc power supply, turn on the TiZrAlCrSi target arc power supply to deposit the TiZrAlCrSi layer, the target material is Ti 0.4 Zr 0.25 Al 0.25 Cr 0.05 Si 0.05 , set the current to 90~120A, bias voltage -50~-350V, and continue for 2~10min; after the bonding layer is formed, turn off the TiZrAlCrSi target arc power supply;
[0102] Step 4: Deposit transition layer: Set the rotation speed to 1r / min, adjust the flow rate of nitrogen and argon, maintain the vacuum to 3.6Pa (nitrogen-argon partial pressure ratio is 1:2), turn on the TiZrAlCr target arc power supply to deposit the TiZrAlCrN layer, and the target material is Ti 0.50 Zr 0.25 Al 0.15 Cr 0.10 , set the current to 90~120A, bias voltage -50~-350V, duration 50min; turn off the TiZrAlCr target arc power supply, turn on the TiZrAlCrSi target arc power supply to deposit the TiZrAlCrSiN layer, the target material is Ti 0.4 Zr 0.25 Al 0.25 Cr 0.05 Si 0.05, Set the current to 90-120A, the bias voltage to -50--350V, and last for 50min; after the transition layer is formed, turn off the TiZrAlCrSi target arc power supply;
[0103] Step 5: Deposition of functional layer: Turn on the arc power supply of TiZrAlCr target, the target material is Ti 0.50 Zr 0.25 Al 0.15 Cr 0.10 , and turn on the TiZrAlCrSi target arc power supply at the same time. The target material is Ti 0.4 Zr 0.25 Al 0.25 Cr 0.05 Si 0.05 , set the rotation speed to increase from 1r / min to 5r / min at the end of coating, set the current to 90-120A, the bias voltage to -50--350V, the duration to 90min, and deposit TiZrAlCrN / TiZrAlCrSiN functional layer;
[0104] Step 6: After the coating is completed, the film is cooled in the furnace and then taken out of the furnace to complete the preparation.
[0105] The novel titanium-zirconium-based superhard tool coating prepared in this embodiment includes a bonding layer, a transition layer and a functional layer deposited in sequence; the bonding layer includes a TiZrAlCr layer and a TiZrAlCrSi layer deposited in sequence, the transition layer includes a TiZrAlCrN layer and a TiZrAlCrSiN layer deposited in sequence, and the functional layer includes a periodically alternately deposited TiZrAlCrN layer and a TiZrAlCrSiN layer;
[0106] Among them, the chemical composition and mass percentage of the TiZrAlCr layer are: Ti: 50%, Zr: 25%, Al: 15%, Cr: 10%; the chemical composition and mass percentage of the TiZrAlCrSi layer are: Ti: 40%, Zr: 25%, Al: 25%, Cr: 5%, Si: 5%; the chemical composition and mass percentage of the TiZrAlCrN layer are: Ti: 25%, Zr: 12.5%, Al: 7.5%, Cr: 5%, N: 50%; the chemical composition and mass percentage of the TiZrAlCrSiN layer are: Ti: 20%, Zr: 12.5%, Al: 12.5%, Cr: 2.5%, Si: 2.5%, N: 50%.
[0107] Example 5
[0108] The present invention provides a method for preparing a novel titanium-zirconium-based superhard tool coating, comprising the following steps:
[0109] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0110] Step 2: MEVVA ion implantation: Place the cleaned sample into the coating furnace and evacuate to 5×10 -2 After Pa, the auxiliary heating source is turned on, the substrate is heated to 400-500℃ and kept warm for 60min, and then the MEVVA power supply is turned on for ion implantation; wherein, the parameter settings are: the cathode is selected as Ti, the extraction voltage is 10-15kV, the trigger frequency is 0-15Hz, the target current is controlled to 80-12mA, and the injection time is 30min;
[0111] Step 3: After the injection is completed, deposit the bonding layer: set the rotation speed to 1r / min, adjust the argon flow rate to maintain the vacuum at 1.0-1.2Pa, turn on the TiZrAlCr target arc power supply to deposit the TiZrAlCr layer, and the target material is Ti 0.55 Zr 0.25 Al 0.10 Cr 0.10, set the current to 90~120A, bias voltage -50~-350V, and last for 2~10min; turn off the TiZrAlCr target arc power supply, turn on the TiZrAlCrSi target arc power supply to deposit the TiZrAlCrSi layer, the target material is Ti 0.50 Zr 0.30 Al 0.10 Cr 0.05 Si 0.05 , set the current to 90~120A, bias voltage -50~-350V, and continue for 2~10min; after the bonding layer is formed, turn off the arc power supply of TiZrAlCrSi target;
[0112] Step 4: Deposit transition layer: Set the rotation speed to 1r / min, adjust the flow rate of nitrogen and argon, maintain the vacuum to 3.6Pa (nitrogen-argon partial pressure ratio is 1:2), turn on the TiZrAlCr target arc power supply to deposit the TiZrAlCrN layer, and the target material is Ti 0.55 Zr 0.25 Al 0.10 Cr 0.10 , set the current to 90~120A, bias voltage -50~-350V, duration 60min; turn off the TiZrAlCr target arc power supply, turn on the TiZrAlCrSi target arc power supply to deposit the TiZrAlCrSiN layer, the target material is Ti 0.50 Zr 0.30 Al 0.10 Cr 0.05 Si 0.05, Set the current to 90-120A, the bias voltage to -50--350V, and last for 60min; after the transition layer is formed, turn off the TiZrAlCrSi target arc power supply;
[0113] Step 5: Deposition of functional layer: Turn on the arc power supply of TiZrAlCr target, the target material is Ti 0.55 Zr 0.25 Al 0.10 Cr 0.10 , and turn on the TiZrAlCrSi target arc power supply at the same time. The target material is Ti 0.50 Zr 0.30 Al 0.10 Cr 0.05 Si 0.05 , set the rotation speed to increase from 1r / min to 5r / min at the end of coating, set the current to 90-120A, the bias voltage to -50--350V, the duration to 80min, and deposit TiZrAlCrN / TiZrAlCrSiN functional layer;
[0114] Step 6: After the coating is completed, the film is cooled in the furnace and then taken out of the furnace to complete the preparation.
[0115] The novel titanium-zirconium-based superhard tool coating prepared in this embodiment includes a bonding layer, a transition layer and a functional layer deposited in sequence; the bonding layer includes a TiZrAlCr layer and a TiZrAlCrSi layer deposited in sequence, the transition layer includes a TiZrAlCrN layer and a TiZrAlCrSiN layer deposited in sequence, and the functional layer includes a periodically alternately deposited TiZrAlCrN layer and a TiZrAlCrSiN layer;
[0116] Among them, the chemical composition and mass percentage of the TiZrAlCr layer are: Ti: 55%, Zr: 25%, Al: 10%, Cr: 10%; the chemical composition and mass percentage of the TiZrAlCrSi layer are: Ti: 50%, Zr: 30%, Al: 10%, Cr: 5%, Si: 5%; the chemical composition and mass percentage of the TiZrAlCrN layer are: Ti: 27.5%, Zr: 12.5%, Al: 5%, Cr: 5%, N: 50%; the chemical composition and mass percentage of the TiZrAlCrSiN layer are: Ti: 25%, Zr: 15%, Al: 5%, Cr: 2.5%, Si: 2.5%, N: 50%.
[0117] Comparative Example 1
[0118] The present invention provides a method for preparing a novel titanium-zirconium-based superhard tool coating, comprising the following steps:
[0119] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0120] Step 2: MEVVA ion implantation: Place the cleaned sample into the coating furnace and evacuate to 5×10 -2 After Pa, the auxiliary heating source is turned on, the substrate is heated to 400-500℃ and kept warm for 60min, and then the MEVVA power supply is turned on for ion implantation; wherein, the parameter settings are: the cathode is selected as Ti, the extraction voltage is 10-15kV, the trigger frequency is 0-15Hz, the target current is controlled to 80-12mA, and the injection time is 30min;
[0121] Step 3: After the injection is completed, deposit the bonding layer: set the rotation speed to 1r / min, adjust the argon flow rate to maintain the vacuum at 1.0-1.2Pa, turn on the TiZrAlCr target arc power supply to deposit the TiZrAlCr layer, and the target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.10, set the current to 90~120A, bias voltage -50~-350V, and last for 2~10min; turn off the TiZrAlCr target arc power supply, turn on the TiZrAlCrSi target arc power supply to deposit the TiZrAlCrSi layer, the target material is Ti 0.4 Zr 0.25 Al 0.25 Cr 0.05 Si 0.05 , set the current to 90~120A, bias voltage -50~-350V, and continue for 2~10min; after the bonding layer is formed, turn off the TiZrAlCrSi target arc power supply;
[0122] Step 4: Deposit the transition layer: Set the rotation speed to 1r / min, adjust the flow rate of nitrogen and argon, maintain the vacuum to 2.4Pa (nitrogen-argon partial pressure ratio is 1:2), turn on the TiZrAlCr target arc power supply to deposit the TiZrAlCrN layer, and the target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.10 , set the current to 90~120A, bias voltage -50~-350V, duration 5min; turn off the TiZrAlCr target arc power supply, turn on the TiZrAlCrSi target arc power supply to deposit the TiZrAlCrSiN layer, the target material is Ti 0.4 Zr 0.25 Al 0.25 Cr 0.05 Si 0.05 , set the current to 90~120A, bias voltage -50~-350V, and last for 5min; after the transition layer is formed, turn off the TiZrAlCrSi target arc power supply;
[0123] Step 5: Deposition of functional layer: Turn on the arc power supply of TiZrAlCr target, the target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.10 , and turn on the TiZrAlCrSi target arc power supply at the same time. The target material is Ti 0.4 Zr 0.25 Al 0.25 Cr 0.05 Si 0.05 , set the rotation speed to increase from 1r / min to 5r / min at the end of coating, set the current to 90-120A, the bias voltage to -50--350V, the duration to 120min, and deposit TiZrAlCrN / TiZrAlCrSiN functional layer;
[0124] Step 6: After the coating is completed, the film is cooled in the furnace and then taken out of the furnace to complete the preparation.
[0125] The novel titanium-zirconium-based superhard tool coating prepared in this comparative example includes a bonding layer, a transition layer and a functional layer deposited in sequence; the bonding layer includes a TiZrAlCr layer and a TiZrAlCrSi layer deposited in sequence, the transition layer includes a TiZrAlCrN layer and a TiZrAlCrSiN layer deposited in sequence, and the functional layer includes a periodically alternately deposited TiZrAlCrN layer and a TiZrAlCrSiN layer;
[0126] Among them, the chemical composition and mass percentage of the TiZrAlCr layer are: Ti: 40%, Zr: 25%, Al: 25%, Cr: 10%; the chemical composition and mass percentage of the TiZrAlCrSi layer are: Ti: 40%, Zr: 25%, Al: 25%, Cr: 5%, Si: 5%; the chemical composition and mass percentage of the TiZrAlCrN layer are: Ti: 20%, Zr: 12.5%, Al: 12.5%, Cr: 5%, N: 50%; the chemical composition and mass percentage of the TiZrAlCrSiN layer are: Ti: 20%, Zr: 12.5%, Al: 12.5%, Cr: 2.5%, Si: 2.5%, N: 50%.
[0127] Comparative Example 2
[0128] The present invention provides a novel method for preparing a titanium-zirconium-based superhard tool coating, comprising the following steps:
[0129] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0130] Step 2: MEVVA ion implantation: Place the cleaned sample into the coating furnace and evacuate to 5×10 -2 After Pa, the auxiliary heating source is turned on, the substrate is heated to 400-500℃ and kept warm for 60min, and then the MEVVA power supply is turned on for ion implantation; wherein, the parameter settings are: the cathode is selected as Ti, the extraction voltage is 10-15kV, the trigger frequency is 0-15Hz, the target current is controlled to 80-12mA, and the injection time is 30min;
[0131] Step 3: After the injection is completed, deposit the bonding layer: set the rotation speed to 1r / min, adjust the argon flow rate to maintain the vacuum at 1.0-1.2Pa, turn on the TiZrAlCr target arc power supply to deposit the TiZrAlCr layer, and the target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.10, set the current to 90~120A, bias voltage -50~-350V, and last for 2~10min; turn off the TiZrAlCr target arc power supply, turn on the TiZrAlCrSi target arc power supply to deposit the TiZrAlCrSi layer, the target material is Ti 0.4 Zr 0.25 Al 0.25 Cr 0.05 Si 0.05 , set the current to 90~120A, bias voltage -50~-350V, and continue for 2~10min; after the bonding layer is formed, turn off the arc power supply of TiZrAlCrSi target;
[0132] Step 4: Deposit the transition layer: Set the rotation speed to 1r / min, adjust the flow rate of nitrogen and argon, maintain the vacuum to 2.4Pa (nitrogen-argon partial pressure ratio is 1:2), turn on the TiZrAlCr target arc power supply to deposit the TiZrAlCrN layer, and the target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.10 , set the current to 90~120A, bias voltage -50~-350V, duration 20min; turn off the TiZrAlCr target arc power supply, turn on the TiZrAlCrSi target arc power supply to deposit the TiZrAlCrSiN layer, the target material is Ti 0.4 Zr 0.25 Al 0.25 Cr 0.05 Si 0.05, Set the current to 90-120A, the bias voltage to -50--350V, and continue for 20min; after the transition layer is formed, turn off the TiZrAlCrSi target arc power supply;
[0133] Step 5: Deposition of functional layer: Turn on the arc power supply of TiZrAlCr target, the target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.10 , and turn on the TiZrAlCrSi target arc power supply at the same time. The target material is Ti 0.4 Zr 0.25 Al 0.25 Cr 0.05 Si 0.05 , set the rotation speed to increase from 1r / min to 5r / min at the end of coating, set the current to 90-120A, the bias voltage to -50--350V, the duration to 50min, and deposit TiZrAlCrN / TiZrAlCrSiN functional layer;
[0134] Step 6: After the coating is completed, the film is cooled in the furnace and then taken out of the furnace to complete the preparation.
[0135] The novel titanium-zirconium-based superhard tool coating prepared in this comparative example includes a bonding layer, a transition layer and a functional layer deposited in sequence; the bonding layer includes a TiZrAlCr layer and a TiZrAlCrSi layer deposited in sequence, the transition layer includes a TiZrAlCrN layer and a TiZrAlCrSiN layer deposited in sequence, and the functional layer includes a periodically alternately deposited TiZrAlCrN layer and a TiZrAlCrSiN layer;
[0136] Among them, the chemical composition and mass percentage of the TiZrAlCr layer are: Ti: 40%, Zr: 25%, Al: 25%, Cr: 10%; the chemical composition and mass percentage of the TiZrAlCrSi layer are: Ti: 40%, Zr: 25%, Al: 25%, Cr: 5%, Si: 5%; the chemical composition and mass percentage of the TiZrAlCrN layer are: Ti: 20%, Zr: 12.5%, Al: 12.5%, Cr: 5%, N: 50%; the chemical composition and mass percentage of the TiZrAlCrSiN layer are: Ti: 20%, Zr: 12.5%, Al: 12.5%, Cr: 2.5%, Si: 2.5%, N: 50%.
[0137] Comparative Example 3
[0138] The present invention provides a novel method for preparing a titanium-zirconium-based superhard tool coating, comprising the following steps:
[0139] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0140] Step 2: MEVVA ion implantation: Place the cleaned sample into the coating furnace and evacuate to 5×10 -2 After Pa, the auxiliary heating source is turned on, the substrate is heated to 400-500℃ and kept warm for 60min, and then the MEVVA power supply is turned on for ion implantation; wherein, the parameter settings are: the cathode is selected as Ti, the extraction voltage is 10-15kV, the trigger frequency is 0-15Hz, the target current is controlled to 80-12mA, and the injection time is 30min;
[0141] Step 3: After the injection is completed, deposit the bonding layer: set the rotation speed to 1r / min, adjust the argon flow rate to maintain the vacuum at 1.0-1.2Pa, turn on the TiZrAlCr target arc power supply to deposit the TiZrAlCr layer, and the target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.10, set the current to 90~120A, bias voltage -50~-350V, and last for 2~10min; turn off the TiZrAlCr target arc power supply, turn on the TiZrAlCrSi target arc power supply to deposit the TiZrAlCrSi layer, the target material is Ti 0.4 Zr 0.25 Al 0.25 Cr 0.05 Si 0.05 , set the current to 90~120A, bias voltage -50~-350V, and continue for 2~10min; after the bonding layer is formed, turn off the arc power supply of TiZrAlCrSi target;
[0142] Step 4: Deposit the transition layer: Set the rotation speed to 1r / min, adjust the flow rate of nitrogen and argon, maintain the vacuum to 2.4Pa (nitrogen-argon partial pressure ratio is 1:2), turn on the TiZrAlCr target arc power supply to deposit the TiZrAlCrN layer, and the target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.10 , set the current to 90~120A, bias voltage -50~-350V, duration 20min; turn off the TiZrAlCr target arc power supply, turn on the TiZrAlCrSi target arc power supply to deposit the TiZrAlCrSiN layer, the target material is Ti 0.4 Zr 0.25 Al 0.25 Cr 0.05 Si 0.05, Set the current to 90-120A, the bias voltage to -50--350V, and continue for 20min; after the transition layer is formed, turn off the TiZrAlCrSi target arc power supply;
[0143] Step 5: Deposition of functional layer: Turn on the arc power supply of TiZrAlCr target, the target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.10 , and turn on the TiZrAlCrSi target arc power supply at the same time. The target material is Ti 0.4 Zr 0.25 Al 0.25 Cr 0.05 Si 0.05 , set the rotation speed to increase from 1r / min to 5r / min at the end of coating, set the current to 90-120A, the bias voltage to -50--350V, the duration to 150min, and deposit TiZrAlCrN / TiZrAlCrSiN functional layer;
[0144] Step 6: After the coating is completed, the film is cooled in the furnace and then taken out of the furnace to complete the preparation.
[0145] The novel titanium-zirconium-based superhard tool coating prepared in this comparative example includes a bonding layer, a transition layer and a functional layer deposited in sequence; the bonding layer includes a TiZrAlCr layer and a TiZrAlCrSi layer deposited in sequence, the transition layer includes a TiZrAlCrN layer and a TiZrAlCrSiN layer deposited in sequence, and the functional layer includes a periodically alternately deposited TiZrAlCrN layer and a TiZrAlCrSiN layer;
[0146] Among them, the chemical composition and mass percentage of the TiZrAlCr layer are: Ti: 40%, Zr: 25%, Al: 25%, Cr: 10%; the chemical composition and mass percentage of the TiZrAlCrSi layer are: Ti: 40%, Zr: 25%, Al: 25%, Cr: 5%, Si: 5%; the chemical composition and mass percentage of the TiZrAlCrN layer are: Ti: 20%, Zr: 12.5%, Al: 12.5%, Cr: 5%, N: 50%; the chemical composition and mass percentage of the TiZrAlCrSiN layer are: Ti: 20%, Zr: 12.5%, Al: 12.5%, Cr: 2.5%, Si: 2.5%, N: 50%.
[0147] Comparative Example 4
[0148] The present invention provides a method for preparing a novel titanium-zirconium-based superhard tool coating, comprising the following steps:
[0149] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0150] Step 2: MEVVA ion implantation: Place the cleaned sample into the coating furnace and evacuate to 5×10 -2 After Pa, the auxiliary heating source is turned on, the substrate is heated to 400-500℃ and kept warm for 60min, and then the MEVVA power supply is turned on for ion implantation; wherein, the parameter settings are: the cathode is selected as Ti, the extraction voltage is 10-15kV, the trigger frequency is 0-15Hz, the target current is controlled to 80-12mA, and the injection time is 30min;
[0151] Step 3: After the injection is completed, deposit the bonding layer: set the rotation speed to 1r / min, adjust the argon flow rate to maintain the vacuum at 1.0-1.2Pa, turn on the TiZrAlCr target arc power supply to deposit the TiZrAlCr layer, and the target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.10, set the current to 90~120A, bias voltage -50~-350V, and last for 2~10min; turn off the TiZrAlCr target arc power supply, turn on the TiZrAlCrSi target arc power supply to deposit the TiZrAlCrSi layer, the target material is Ti 0.4 Zr 0.25 Al 0.25 Cr 0.05 Si 0.05 , set the current to 90~120A, bias voltage -50~-350V, and continue for 2~10min; after the bonding layer is formed, turn off the arc power supply of TiZrAlCrSi target;
[0152] Step 4: Deposit transition layer: Set the rotation speed to 1r / min, adjust the flow rate of nitrogen and argon, maintain the vacuum to 1.0Pa (nitrogen and argon partial pressure ratio is 1:2), turn on the TiZrAlCr target arc power supply to deposit the TiZrAlCrN layer, and the target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.10 , set the current to 90~120A, bias voltage -50~-350V, duration 20min; turn off the TiZrAlCr target arc power supply, turn on the TiZrAlCrSi target arc power supply to deposit the TiZrAlCrSiN layer, the target material is Ti 0.4 Zr 0.25 Al 0.25 Cr 0.05 Si 0.05, Set the current to 90-120A, the bias voltage to -50--350V, and continue for 20min; after the transition layer is formed, turn off the TiZrAlCrSi target arc power supply;
[0153] Step 5: Deposition of functional layer: Turn on the arc power supply of TiZrAlCr target, the target material is Ti 0.40 Zr 0.25 Al 0.25 Cr 0.10 , and turn on the TiZrAlCrSi target arc power supply at the same time. The target material is Ti 0.4 Zr 0.25 Al 0.25 Cr 0.05 Si 0.05 , set the rotation speed to increase from 1r / min to 5r / min at the end of coating, set the current to 90-120A, the bias voltage to -50--350V, the duration to 120min, and deposit TiZrAlCrN / TiZrAlCrSiN functional layer;
[0154] Step 6: After the coating is completed, the film is cooled in the furnace and then taken out of the furnace to complete the preparation.
[0155] The novel titanium-zirconium-based superhard tool coating prepared in this comparative example includes a bonding layer, a transition layer and a functional layer deposited in sequence; the bonding layer includes a TiZrAlCr layer and a TiZrAlCrSi layer deposited in sequence, the transition layer includes a TiZrAlCrN layer and a TiZrAlCrSiN layer deposited in sequence, and the functional layer includes a periodically alternately deposited TiZrAlCrN layer and a TiZrAlCrSiN layer;
[0156] Among them, the chemical composition and mass percentage of the TiZrAlCr layer are: Ti: 40%, Zr: 25%, Al: 25%, Cr: 10%; the chemical composition and mass percentage of the TiZrAlCrSi layer are: Ti: 40%, Zr: 25%, Al: 25%, Cr: 5%, Si: 5%; the chemical composition and mass percentage of the TiZrAlCrN layer are: Ti: 20%, Zr: 12.5%, Al: 12.5%, Cr: 5%, N: 50%; the chemical composition and mass percentage of the TiZrAlCrSiN layer are: Ti: 20%, Zr: 12.5%, Al: 12.5%, Cr: 2.5%, Si: 2.5%, N: 50%.
[0157] Test Case
[0158] In the present invention, the following performance tests are performed on Examples 1 to 5 and Comparative Examples 1 to 4 respectively:
[0159] Nanohardness test: Micro Materials Vantage nanomechanical system, based on the technical specification of JB / T12721-2016 "Solid Material In-situ Nanoindentation Scratch Tester", uses the commonly used diamond tip, 10 points are tested on each sample, and then the average value is taken. The experiment was conducted at room temperature and 500℃, with a maximum load of 50mN, a loading time of 10s, and an unloading time of 10s, to ensure that the indentation depth does not exceed 1 / 10 of the coating thickness.
[0160] Vickers hardness test: HXD-1000 Vickers microhardness tester, based on GB / T 4340.1-2009 "Metallic materials Vickers hardness test Part 1: Test method", at the 200gf force position, the loading and holding time is set to 10s, and 10 points are measured for each sample.
[0161] Membrane-substrate bonding strength test: RST3 macro scratch tester, scratch length 3 mm, scratch displacement speed 3 mm / min, starting load 1 N, and ending load 200 N.
[0162] Turning experiment: The turning material is stainless steel 316L, 150-180HB, and the blade model is CCMT09T30. Semi-finishing, Vc = 150m / min, Fn = 0.2mm / r, Ap = 0.5mm. Life judgment standard: Take a photo once every 3 minutes, and the back tool wear value Vb> 0.3mm is judged as failure.
[0163] As shown in Table 1 and Table 2, the test results are as follows:
[0164] Table 1 Test results
[0165]
[0166] Table 2 Test results
[0167]
[0168] Figure 2a , 3a , 4a, 5a, and 6a are surface morphology diagrams of the examples of the present invention. It can be seen that the surface quality of the prepared coating is good, and there are some white bright particles. This is because during the coating deposition process, the arc temperature is very high, causing the surface of the target material to melt, and the unionized neutral atoms will be ejected in the form of droplets and deposited on the surface of the film to form droplet contamination. It can be seen from the examples that when the target material composition is similar, reducing the coating time or reducing the deposition pressure is beneficial to improving the surface quality of the prepared coating.
[0169] Figure 2c , 3c , 4c, 5c, and 6c are cross-sectional morphology diagrams of the examples of the present invention. It can be seen that the thickness of the prepared coating is controllable, and the interface between the layers and the substrate is clear and flat. Due to the high deposition speed and the dense coating, the bonding layer, transition layer, and functional layer are not clearly observed in the figure.
[0170] like Figure 8 As shown, after the bonding strength test, the bonding strength of the prepared coatings exceeds 70N, which can ensure that there will be no premature cracking in the dry cutting state.
[0171] Figure 2b , 3b , 4b, 5b, 6b are the nano-hardness test results of the examples of the present invention. It can be seen that under the same test conditions, the room temperature hardness of the coating exceeds 35Gpa, and the high temperature hardness exceeds 29Gpa. Compared with traditional TiN, CrN, AlTiN, AlCrSiN and other coatings, the room temperature hardness is increased by 20%-50%, and the high temperature hardness is increased by 40%-80%. The titanium zirconium-based superhard tool coating prepared in the examples of the present application has higher room temperature and high temperature hardness, and is also resistant to high temperature wear.
[0172] Under the same tool structure and cutting conditions, the service life of the titanium zirconium-based superhard tool coating prepared by the present invention in dry cutting of 316L is as follows: Figure 7 As shown in the figure, the dry cutting time of the embodiments shown is more than 27 minutes, and the maximum cutting time can reach 39 minutes, which is 107% longer than the AlTiN coated tool with the most mature tool application in the prior art, and has excellent cutting performance.
[0173] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for preparing a novel titanium-zirconium-based superhard tool coating, characterized in that: The steps include: Step 1: After cleaning the sample to be plated, place it in a coating furnace, evacuate the vacuum, heat the substrate, and perform ion implantation; Step 2, adjusting the argon flow rate to maintain the vacuum state, turning on the TiZrAlCr target arc power supply to deposit the TiZrAlCr layer, turning off the TiZrAlCr target arc power supply, turning on the TiZrAlCrSi target arc power supply to deposit the TiZrAlCrSi layer, and turning off the TiZrAlCrSi target arc power supply after the bonding layer is formed; Step 3, adjusting the flow rate of nitrogen and argon to maintain the vacuum state, turning on the TiZrAlCr target arc power supply to deposit the TiZrAlCrN layer, turning off the TiZrAlCr target arc power supply, turning on the TiZrAlCrSi target arc power supply to deposit the TiZrAlCrSiN layer, and turning off the TiZrAlCrSi target arc power supply after the transition layer is formed; Step 4: Turn on the TiZrAlCr target arc power supply and the TiZrAlCrSi target arc power supply at the same time, deposit the TiZrAlCrN / TiZrAlCrSiN layer, and cool after forming the functional layer to obtain the novel titanium-zirconium-based superhard tool coating.
2. The method for preparing the novel titanium-zirconium-based superhard tool coating according to claim 1, characterized in that: In the step 1, the cleaning process of the sample to be plated includes: immersing the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-drying the surface; and Vacuum to 5×10 -2 Pa, heat to 400-500℃ and keep warm for 60min.
3. The method for preparing the novel titanium-zirconium-based superhard tool coating according to claim 1, characterized in that: In the step 1, the ion implantation conditions include: selecting Ti as the cathode, an extraction voltage of 10-15 kV, a trigger frequency of 0-15 Hz, controlling the target current to 80-120 mA, and an implantation time of 30 min.
4. The method for preparing the novel titanium-zirconium-based superhard tool coating according to claim 2 or 3, characterized in that: In the step 2, the coating speed is set to 1 r / min, and the vacuum state is maintained at 1.0-1.2 Pa.
5. The method for preparing the novel titanium-zirconium-based superhard tool coating according to claim 1, characterized in that: In the step three, the coating speed is set to 1 r / min, the vacuum state is maintained at 2.4-3.6 Pa, and the partial pressure ratio of nitrogen and argon is 1:
2.
6. The method for preparing the novel titanium-zirconium-based superhard tool coating according to claim 1, characterized in that: In the step 4, the rotation speed is set to increase from 1 r / min to 5 r / min before the coating is finished, the vacuum state is maintained at 2.4-3.6 Pa, and the partial pressure ratio of nitrogen and argon is 1:
2.
7. The method for preparing a novel titanium-zirconium-based superhard tool coating according to any one of claims 1 to 3, 5 and 6, characterized in that: Set the TiZrAlCr target to Ti p Zr q Al r Cr s , where p, q, r, s satisfy 0.40≤p≤0.55, 0.25≤q≤0.35, 0.10≤r≤0.25, 0.05≤s≤0.10, p+q+r+s=1, current is 90~120A, bias voltage is -50~-350V, and lasts for 2~10min; Set the TiZrAlCrSi target to Ti a Zr b Al c Cr d Si e , where a, b, c, d, e, satisfy 0.40≤a≤0.55, 0.25≤b≤0.35, 0.10≤c≤0.25, d=0.05, e=0.05, a+b+c+d+e=1, current is 90~120A, bias voltage is -50~-350V, and lasts for 2~10min; and Among them, 0≤|pa|≤0.15, 0≤|qb|≤0.15, 0≤|rc|≤0.15, 0≤|sd|≤0.
10.
8. A new type of titanium-zirconium-based superhard tool coating, characterized in that: The coating is prepared by using the method for preparing a novel titanium-zirconium-based superhard tool coating according to any one of claims 1 to 7, wherein the novel titanium-zirconium-based superhard tool coating comprises a bonding layer, a transition layer and a functional layer deposited in sequence; Wherein, the bonding layer comprises a TiZrAlCr layer and a TiZrAlCrSi layer deposited sequentially, the transition layer comprises a TiZrAlCrN layer and a TiZrAlCrSiN layer deposited sequentially, and the functional layer comprises a TiZrAlCrN layer and a TiZrAlCrSiN layer deposited periodically and alternately; and The chemical composition and mass percentage of the TiZrAlCr layer are: Ti: 40% to 55%, Zr: 25% to 35%, Al: 10% to 25%, Cr: 5% to 10%; The chemical composition and mass percentage of the TiZrAlCrSi layer are: Ti: 40% to 55%, Zr: 25% to 35%, Al: 10% to 25%, Cr: 5%, Si: 5%; The chemical composition and mass percentage of the TiZrAlCrN layer are: Ti: 20% to 27.5%, Zr: 12.5% to 17.5%, Al: 5% to 12.5%, Cr: 2.5% to 5%, N: 50%; The chemical composition and mass percentage of the TiZrAlCrSiN layer are: Ti: 20% to 27.5%, Zr: 12.5% to 17.5%, Al: 5% to 12.5%, Cr: 2.5%, Si: 2.5%, and N: 50%.
9. The novel titanium-zirconium-based superhard tool coating according to claim 8, characterized in that: The thickness of the novel titanium-zirconium-based superhard tool coating is 3 to 6 μm.
10. Application of a new type of titanium zirconium-based superhard tool coating in superhard, tough and high temperature resistant cutting tools, characterized in that: Use the novel titanium-zirconium-based superhard tool coating as claimed in claim 8.
Citation Information
Patent Citations
Hard coating and hard coating-covered member
CN107532280A
Anti-oxidation high-entropy nitride coating as well as preparation method and application thereof
CN116641022A
High-temperature alloy cutting coating tool and preparation method thereof
CN117026147A
